PARAOXANASE ACTIVITY AND ITS CONCENTRATION IN TYPE2 DIABETES MELLITUS - DR.SK.DEEPTHI; DR.G.AMAR RAGHU NARAYAN (International Journal of Pharma and Bio Sciences, 2012)
Human serum paraoxonase is a high density lipoprotein (HDL) associated enzyme capable of hydrolyzing diverse substrates from organophosphate toxins to oxidized Phospholipids and possibly in the prevention of LDL lipid peroxidation. We investigated the serum activity and concentration of paraoxonase levels and fasting blood glucose levels in 104 subjects (42 patients with type2diabetes without Complications, 20 patients with type2 diabetes with complications, 42 controls were taken. Patients with type2 diabetes with complications had lower Paraoxonase activity than those without the complications. These results suggest that decreased PON activity in patients with type2 diabetes were involved with diabetic vascular complications